Magnetic resonance imaging (MRI) brain findings in severe pre–eclampsia/eclampsia - RV, Ganesh; SF, Lee; I, Ghazali; Zainuddin, Ahmad Murad; Paul, Ng; Abd. Aziz, Azian; S, Azlin; AS, Devaraj (Obstetrical & Gynaecological Society of Malaysia, 2006)
MRI is mainly used in obstetrics in the evaluation of maternal bony pelvis, the cervix for cervical incompetence, localisation of placental site, diagnosis of gestational trophoblastic disease and its severity, and in diagnosing fetal malformations such as renal agenesis. This study aimed to correlate the MRI brain findings in patients with symptomatic and asymptomatic severe pre – eclampsia / eclampsia, and to determine the value of MRI as a predictive diagnostic tool in the management of such cases. This is a prospective descriptive study of 30 pregnant mothers with clinical signs and symptoms of pre-eclampsia / severe pre-eclampsia / eclampsia admitted to the pre-eclampsia room (High Dependency Unit) of the labour room of the Hospital Tengku Ampuan Afzan Kuantan Pahang, Malaysia from 1st January 2004 to 30th June 2004. General findings indicate that there were no conclusive results with regard to the correlation between the MRI brain changes seen in both groups of patients.